Reexamination of Heteronaias heterodoxa (Selys, 1878) (Odonata: Corduliidae), with larval redescription, comparative notes on Asian Corduliidae larvae, and biogeographic significance - Keetapithchayakul, Tosaphol Saetung; Kim, Junggonn; Phan, Quoc Toan; Digma, Jonathan Rodrin (Zootaxa, 2026)
Heteronaias Needham & Gyger, 1937 is a monotypic genus represented solely by Heteronaias heterodoxa (Selys, 1878), a poorly documented corduliid. Based on reared specimens from Luzon, Philippines, we provide a detailed larval description, notes on adult morphology, and distributional data. Adult characters, particularly the vesica spermalis of male and female terminalia, are redescribed and illustrated. The larva is distinguished by a flattened body, 9–13 premental setae, 8–11 palpal setae, a poorly developed ligula, middorsal protuberances on abdominal segments 6–10, and a distinct episternal apophysis. Comparative analysis with Asian corduliid genera highlights diagnostic larval features valuable for taxonomy and phylogenetic studies. Larvae inhabit shaded forest streams and emerge on rock surfaces, showing rheophilic adaptations comparable to those of Zygonyx Selys in Hagen, 1867 (Libellulidae). Distributional records confirm that H. heterodoxa is endemic to the Philippines.